(untitled) (Intent Research Scientific Journal, 2023)
This review discusses articles in the last 10 years about the etiology, pathogenesis, and clinical manifestations of ETEC, as well as gut microbiota-mediated resistance to colonization, its interactions in human small intestine, prevention strategies and most importantly modern diagnostic methods using cutting-edge technologies which provide new insights in reducing adverse human health impacts.